Promoting oral care in the preschool child: effects of a playful learning intervention - Cecília Helena de Siqueira Sigaud; Bruna Rodrigues dos Santos; Priscila Costa; Aurea Tamami Minagawa Toriyama
ABSTRACT Objective: To compare the number of appropriate behaviors for tooth brushing before and after a playful learning intervention with preschool children. Method: A quasi-experimental, quantitative, before and after study design was conducted in an early childhood educational institution, with children between three and five years of age. The intervention consisted of three meetings with educational activities about tooth brushing, whose outcome was evaluated by means of observation of ten behaviors suitable for tooth brushing. Results: Forty-four children participated in the study. The mean of adequate behaviors was 4.4 before the intervention, and 8.5 after the intervention. A significant increase in the adoption of appropriate behaviors for tooth brushing (p <0.01) was identified. Conclusion: Nurses can enhance oral health promotion actions with preschoolers in preschool institution using playful learning interventions